2015
DOI: 10.1016/j.jclinepi.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Parental depression and child well-being: young children's self-reports helped addressing biases in parent reports

Abstract: Depression of mothers and fathers affects young children's well-being. However, if parents reported about their own depression and about child problems, associations were inflated. To accurately estimate effects of parental depression, multiple-source data including young children's perspectives must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 42 publications
1
49
0
4
Order By: Relevance
“…The differences between the two studies might be explained by the design of our study (cross‐sectional vs. longitudinal and repeated measures design) and, most importantly by a different informant (a teacher report vs. a mother report) as a measure for outcome. An earlier study showed that, when maternal reports are used for both the determinant and the outcome measure, the associations were strongly inflated (Ringoot et al., ). Thus, when mothers report both picky eating and problem behavior of the child, any observed association of picky eating with behavior and emotional problems is prone to reporter bias.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the two studies might be explained by the design of our study (cross‐sectional vs. longitudinal and repeated measures design) and, most importantly by a different informant (a teacher report vs. a mother report) as a measure for outcome. An earlier study showed that, when maternal reports are used for both the determinant and the outcome measure, the associations were strongly inflated (Ringoot et al., ). Thus, when mothers report both picky eating and problem behavior of the child, any observed association of picky eating with behavior and emotional problems is prone to reporter bias.…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently found that depression alters the reporting of parenting and child outcomes (24). Studies using multi-method and multi-informant or observer-based measures are necessary to address this issue (25).…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…Beyond just an assessment/statistical nuance, mother-father discrepancy in these ratings may hinder accurate classification and treatment of child psychopathology (see De Los Reyes & Kazdin, 2005 for an overview). Understanding father-mother discrepancies in informant ratings of children’s internalizing symptoms in families in which one or both parents have substance use disorder (SUD) may be especially valuable given that children of substance-abusing parents have greater risk for both depression and anxiety as compared to peers (Bountress & Chassin, 2015; Hussong, Flora, Curran, Chassin, & Zucker, 2008; Ringoot et al, 2015). Further, both parent SUD and parent mental health problems may be associated with parents’ ability to accurately rate their children’s symptoms (Bingham, Loukas, Fitzgerald, & Zucker, 2003; Hennigan, O’Keefe, Noether, Rinehart, & Russel, 2006; Ringoot et al, 2015) and may impact discrepancy in parent ratings.…”
Section: Introductionmentioning
confidence: 99%